2019
DOI: 10.1177/0894845319833189
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Job Insecurity and Performance: Hindrance or Challenge Effect?

Abstract: This study aims to propose a theoretical model that explains the psychological processes underlying the job insecurity-performance relationship. To accomplish this goal, we draw on a twodimensional stressor framework. Job insecurity may undermine performance through a hindrance effect, because it causes strain reactions and withdrawal behaviours. In contrast, it can trigger productive behaviours as a form of job preservation strategy, when reacting actively. These competing predictions are integrated in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 50 publications
9
72
0
5
Order By: Relevance
“…The results are consistent with much of the research on job insecurity and how it relates to various performance outcomes, including two meta-analyses on job insecurity that included job performance [4,9]. The finding that job insecurity appears to be detrimental for employee performance is also contrary to those studies suggesting that experiences of job insecurity will make employees work harder [16,17]. The fact that we did not find any relationship between job insecurity and creativity could be attributed to several different factors, for example, that while job insecurity is associated with other types of performance [69,74], it is not related to creative and innovative performance.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The results are consistent with much of the research on job insecurity and how it relates to various performance outcomes, including two meta-analyses on job insecurity that included job performance [4,9]. The finding that job insecurity appears to be detrimental for employee performance is also contrary to those studies suggesting that experiences of job insecurity will make employees work harder [16,17]. The fact that we did not find any relationship between job insecurity and creativity could be attributed to several different factors, for example, that while job insecurity is associated with other types of performance [69,74], it is not related to creative and innovative performance.…”
Section: Discussionsupporting
confidence: 80%
“…More specifically, our results replicate previous meta-analyses that have found that job insecurity is detrimental for employee performance [4,9], and also extend existing research by investigating a wider range of performance outcomes (task performance, contextual performance, counterproductive work behavior, creativity, and safety performance). The findings that job insecurity was associated with lower levels of task, contextual, and safety performance and higher levels of counterproductive behavior (but not with creativity on a general level) diverge from those of certain other studies which suggest that job insecurity will lead to employees working harder [16,17]. Rather, our results are in line with theories suggesting that job insecurity is associated with impaired performance due to it being a stressor [15] and that it constitutes a breach of the psychological contract [42] or a threat to one’s identity [40].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Individuals in stressful work situations often suffer from health problems such as insomnia [ 13 ]. Most scholars identify job insecurity as an obstructive stressor [ 34 ]. By definition, job insecurity refers to an employee’s fear and worry about becoming unemployed.…”
Section: Theory and Hypothesesmentioning
confidence: 99%